NETIZEN RESPONSES ON TIKTOK REGARDING THE LABUAN BAJO TOURISM TRAGEDY ON THE @detikcom ACCOUNT (DECEMBER 26, 2025) - Hanum, Kurnia; Sazali, Hasan (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze how the TikTok account @detikcom framed the Labuan Bajo tourism tragedy on December 26, 2025, and how netizens responded to the news through the comments section. The novelty of this study lies in its focus on TikTok as a digital public space in the context of the tourism crisis, which is still relatively rarely studied compared to other social media platforms. The study used a qualitative approach with content analysis methods. Data came from approximately 3,500 comments on three TikTok videos, then 300 comments were purposively selected based on three criteria: relevance to the issue, having a clear meaning, and containing substantive responses to the news content. The results showed that the @detikcom news primarily emphasized issues of ship crossing procedures and safety facilities and infrastructure. Of the 300 selected comments, 248 comments could be categorized, while 52 comments were eliminated due to being irrelevant, spam, or ambiguous. Netizen responses were dominated by criticism (98 comments), evaluative (94 comments), emotional (42 comments), and tourism image (14 comments). These findings demonstrate that public responses on TikTok extend beyond emotional expression to include rational assessments of tourism safety governance. Thus, TikTok serves as a discursive arena that shapes public opinion while demonstrating digital social control over tourism safety issues.